Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1074/jbc.m104755200
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of an Alternatively Spliced Form of SR Protein Kinase 1 That Interacts Specifically with Scaffold Attachment Factor-B

Abstract: Serine/arginine protein kinases have been conserved throughout evolution and are thought to play important roles in the regulation of mRNA processing, nuclear import, germline development, polyamine transport, and ion homeostasis. Human SRPK1, which was first identified as a kinase specific for the SR family of splicing factors, is located on chromosome 6p21.2-p21.3. We report here the cloning and characterization of SRPK1a, which is encoded by an alternatively processed transcript derived from the SRPK1 gene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
25

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 53 publications
1
43
0
25
Order By: Relevance
“…Currently, little is known about how SR protein kinases are regulated in cells. It has been hypothesized that the activity of these kinases is modulated through mechanisms involving regulation of their subcellular localization (20,33,42). Recently, Mylonis and Giannakouros have found that protein kinase CK2 directly phosphorylates SRPK1 and enhances its activity (32a), suggesting that SR protein kinases are regulated at multiple levels in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, little is known about how SR protein kinases are regulated in cells. It has been hypothesized that the activity of these kinases is modulated through mechanisms involving regulation of their subcellular localization (20,33,42). Recently, Mylonis and Giannakouros have found that protein kinase CK2 directly phosphorylates SRPK1 and enhances its activity (32a), suggesting that SR protein kinases are regulated at multiple levels in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…SREK1 (also known as SRrp86), for example, has been shown to be antagonised by SAFB [88]. A more generalised effect on splicing could be mediated by an inhibitory interaction between SAFB and the SR protein kinase SRPK1, which phosphorylates specific SR proteins [89,90].…”
Section: Mrna Processingmentioning
confidence: 99%
“…Conversely, weaker interactions may be maintained in the presence of low salt, but there may be a risk of artefactual interactions. [10], hnRNPC [10], hnRNPD [120], hnRNPG [25,84,121], hnRNPI [10], hnRNPK [10,122], hnRNPU [10] SR proteins SRSF1 [33], SRSF7 [26], SRSF9 [26,33], SREK1 [88], SRRM1 [123] SR protein kinase SRPK1 [89] Chromatin CHD1 [72], NCOR [37,71], HDAC3, [37,71] BRG1 [73], Matrin3 [54] Transcription RNAPolII [33], TAF II 68 [124], steroid receptors [67][68][69], P53 [70] Miscellaneous PIAS1 [37], ZO-2 [125], Zbed4 [126] Also, co-immunoprecipitation does not distinguish between direct protein interactions and interactions mediated by 'bridging' molecules, such as other proteins or nucleic acids. Formation of homo-and hetero-dimers of SAFB1 and SAFB2, as well as interactions with several hnRNP proteins, has been observed (see Table 1 for a summary of some of the proteins shown to interact with SAFB proteins).…”
Section: Proteinsmentioning
confidence: 99%
“…regulators including Tra2␤, SF2/ASF, 9G8, SRp30c, YT521B, SRp86, SLM1, T-STAR (also known as SLM2), hnRNP A1 and hnRNP D (Denegri et al, 2001;Hartmann et al, 1999;Li et al, 2003;Nayler et al, 1998b;Stoss et al, 2001;Weighardt et al, 1999) and with protein kinases which phosphorylate splicing regulators (SRPK1 and CLK2) (Nikolakaki et al, 2001). Besides these yeast two hybrid interactions based on SAFB1 protein, very little is known about the existence of real endogenous protein interactions or heterocomplexes.…”
Section: Introductionmentioning
confidence: 99%